2018
DOI: 10.29196/jubpas.v26i8.1647
|View full text |Cite
|
Sign up to set email alerts
|

The Association of TSHR Gene rs2268458 Polymorphism with Hypothyroidism in Females of Babylon Province-Iraq

Abstract: The Aim: To evaluate the association of TSHR gene polymorphism rs2268458 with some Physio-biochemical parameters among hypothyroidism women. Methods: This study included 51 hypothyroidism women and 43 healthy women as a control group. Some Physio-biochemical (body mass index (BMI), cytochrome 450 1A1 (CYP1A1), calcium, and phosphorus) and hormonal assay (Osteopontin (OPN), thyroid stimulating hormone (TSH), fT3, fT4 and Calcitonin (CT)) assay were performed. Genotyping of rs-2268458 of TSHR gene was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…this result was consistent with a case-control study between hypothyroidism and healthy controls, there was no signifi cant difference in the TSHR rs2268458 polymorphisms and allele frequency between hypothyroidism group and control group (Al-Azzam et al, 2014) (8) . While this result Inconsistent with the result of case-control study among Iraqi patients with hypothyroidism indicated a signifi cant differences in rs2268458 between hypothyroidism and control groups (Hussain, et al, 2018) (9) . Yin et al, (2008) demonstrated that the intronic TSHR (rs2268458) was associated with hyperthyroidism but not with hypothyroidism, thus indicating that the TSHR gene has the potential to increase susceptibility to hyperthyroidism that was consistent with our study (10) .…”
Section: Sequence Of Amplifi Ed Thyrotropin Receptor Genementioning
confidence: 65%
“…this result was consistent with a case-control study between hypothyroidism and healthy controls, there was no signifi cant difference in the TSHR rs2268458 polymorphisms and allele frequency between hypothyroidism group and control group (Al-Azzam et al, 2014) (8) . While this result Inconsistent with the result of case-control study among Iraqi patients with hypothyroidism indicated a signifi cant differences in rs2268458 between hypothyroidism and control groups (Hussain, et al, 2018) (9) . Yin et al, (2008) demonstrated that the intronic TSHR (rs2268458) was associated with hyperthyroidism but not with hypothyroidism, thus indicating that the TSHR gene has the potential to increase susceptibility to hyperthyroidism that was consistent with our study (10) .…”
Section: Sequence Of Amplifi Ed Thyrotropin Receptor Genementioning
confidence: 65%
“…SNPs in intron 7 of the TSHR were also found to be associated with GD in Japanese [32], and SNPs in intron 1 of the TSHR were reported to be associated with GD in Caucasians [16]. So the result is, there is an association between rs2268458 with hypothyroidism and it has been con rmed that the allel C has a pathogenic effect on recessive, dominant and codominant but the biggest effect is on recessive allel and it has been perceived that the allel C is a pathogenic allel which is usually heritated more in a recessive pattern [12] In this study, homozygote cases (TT) will not show the symptoms and they only have a 162 bp band, heterozygote cases (TC) show some of the symptoms or some light symtoms and they have 3 bands: 162, 100 and 62 but the homozygote cases (CC), show sever symptoms and they have 2 bands 100 and 62 bp which agrees with the Iraq's study who reported that TSHR rs2268458 polymorphisms were associated with hypothyroidism [12] and disagrees with the Lebanon's study who reported that TSHR rs2268458 polymorphisms were not associated with hypothyroidism and hyperthyroidism [23] According to [17], there was a correlation between relapse of Graves disease and CC genotype of TSHR gene on the rs2268458 of intron 1 [17]. In a study, related to thyroid disease association with polymorphism in Iraq, 73 cases were homozygote (TT), 20 casese were heterozygotes (TC) and 1 case was homozygote (CC) and since all the reseach was done on females, the homozygote(CC) case was a woman [12] but in this study, both men and females were involved and the homozygote case(CC) was a man.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants in the TSHR gene were recognized to be associated with the risk of thyroid diseases [9][10][11]. Previous studies have shown that choromosome 14 is associated with thyroid disorders; particularly hypothyroidism and the most important gene-regions are 35 Mbp, 95 Mbp and 93 Mbp, in proximity to the rs2268458 single-neucleotide polymorphism (SNP) [12][13][14][15] ,which is located on intron 1 of TSHR gene.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli is the leading cause urinary tract infections in both men and women, and it ranks second only to respiratory disorders. [6]. Due to bacteria's ability to excretion several enzymes, such as [ESBL] Extended Spectrum B-lactamase Enzymes [ESBL], metallo B-lactamase [MBL], and hemolysin.…”
Section: Introductionmentioning
confidence: 99%